2016
DOI: 10.1186/s13075-016-1023-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-125b: association with disease activity and the treatment response of patients with early rheumatoid arthritis

Abstract: BackgroundMicroRNAs (miRNAs) are small RNAs that regulate gene expression by targeting mRNA. It was proved that some miRNAs are significantly deregulated in rheumatoid arthritis (RA). MicroRNA-125b negatively regulates expression of TNF-α, which plays a crucial role in RA pathogenesis. The aim of this study was to determine the treatment outcome of patients with early RA based on the expression of circulating and cellular miR-125b.MethodsTotal RNA was isolated from the plasma and peripheral blood mononuclear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Besides, over time, patients with severe cases have to receive surgical interventions, such as total hip arthroplasty. 7 Besides, miRNAs have been regarded as potential pharmacological candidates for therapeutic treatment in RA. miRNAs were initially considered as "junk," because they do not code protein directly.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, over time, patients with severe cases have to receive surgical interventions, such as total hip arthroplasty. 7 Besides, miRNAs have been regarded as potential pharmacological candidates for therapeutic treatment in RA. miRNAs were initially considered as "junk," because they do not code protein directly.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of miRNA-451 in T cells also positively correlated with DAS28 (Smigielska-Czepiel et al 2014 ). Another study has shown that expression of miRNA-125b in peripheral blood mononuclear cells was a better predictor for an optimal treatment outcome after 3 months TNF-α therapy than baseline levels of DAS28, CRP, erythrocyte sedimentation rate (ESR) (Hruskova et al 2016 ). In the recent studies, it has been observed that sera circulating miRNA-29a-3p, miRNA-146a-5p or miRNA-222-3p were associated with spinal changes and/or disease activity assessed by bath ankylosing spondylitis disease activity index (BASDAI) in AS patients (Prajzlerova et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression of neuronal miRs within urothelial tissue captured by punch bladder biopsy could provide insight into the molecular changes that drive age‐related diminished bladder volume sensations and increased urinary retention following onaBoNT‐A injection . miR125b and miR221 are prominent microRNAs in neuronal differentiation, and they are downregulated in neurological disorders . In this study, both miR125b and miR221 were downregulated within the urothelium of patients that developed high PVRs after onaBoNT‐A.…”
Section: Discussionmentioning
confidence: 60%